Peningkatan Literasi Keamanan Digital Bagi Pelaku UMKM Produk Hasil Perikanan Di Desa Mandalle Kecamatan Bajeng Barat - Puput Kusuma Dewi; Mahrus Sabang; Sahban Nur; Abd. Rahmat Karim Haba (Program Studi Manajemen FEB UNM, 2026)
Digital transformation provides increasingly broad opportunities for Micro, Small, and Medium Enterprises (MSMEs), including fishery-product MSMEs, to expand their market reach, improve business efficiency, and utilize various digital transaction services. However, this development is also accompanied by growing cybersecurity risks, such as online fraud, phishing, account hacking, personal data theft, and the misuse of digital information. These challenges are particularly significant for MSME actors who still have limited digital literacy and security awareness. This community service program aimed to enhance the knowledge, skills, and readiness of fishery-product MSME actors in Mandalle Village, Bajeng Barat District, in implementing digital security practices in their business activities. The program employed a participatory and educational approach consisting of four stages: needs identification and an initial survey accompanied by a pre-test, delivery of materials on digital security and the use of Artificial Intelligence, hands-on training, and mentoring and evaluation through a post-test. The initial observation indicated that approximately 85% of participants did not understand the basic concepts of secure digital transactions and had a relatively low level of awareness of various cyber threats. Following the educational and training activities, a comparison of the pre-test and post-test results across 10 indicators showed an improvement in participants’ understanding, particularly in recognizing cybercrime schemes, identifying suspicious messages and links, and understanding appropriate measures to mitigate digital risks. During the practical session, participants were able to implement several security measures, including creating stronger and unique passwords, enabling two-factor authentication on social media accounts and WhatsApp Business, and using GetContact to help identify suspicious phone numbers. The program also increased participants’ confidence in using social media and online transactions to support business development. Overall, the participatory and hands-on training approach was effective in improving the digital security literacy and practical skills of fishery-product MSME actors in Mandalle Village. Continued mentoring and periodic evaluation are still required to ensure that digital security practices are implemented consistently in their daily business activities.